Genome organization and DNA accessibility control antigenic variation in trypanosomes - Müller, Laura S. M.; Cosentino, Raúl O.; Guizetti, Julien (Nature, 2018)
Long-read sequencing allows the assembly of antigen-gene arrays in Trypanosoma brucei and, coupled with deletion experiments, demonstrates that histone variants act as a molecular link between genome architecture, chromatin conformation and antigen variation.